Resistance Analysis of CRISPR/Cas9 Genome-Edited Chili M2 Mutant Lines against Pepper Yellow Leaf Curl Viral Disease - Prasetya, Wandy Murti; Hadiarto, Toto; Enggarini, Wening; Polosoro, Aqwin; Suharsono, Suharsono (Jurnal AgroBiogen, 2021)
Pepper yellow leaf curl virus (PepYLCV) infection transmitted by silverleaf whitefly (Bemisia tabaci [Gennadius]) can decrease chili pepper yield up to 100%. At this moment, there is no chili pepper variety resistant to PepYLCV available. Genome editing approach through CRISPR/Cas9 is an effort to develop variety resistance to the viral infection. The purpose of this study was to obtain M2 lines developed by CRISPR/Cas9 system on proliferating cell nuclear antigen (PCNA) gene for resistance to PepYLCV. A total of four M2 lines (C47-7, L84-2, L84-23, and L120-19) consisting of 60 chili plants were tested for their resistance to PepYLCV. PCR analysis was performed to detect the presence (infection) of the virus. The results showed that a total of 35 plants derived from the four lines were resistant to PepYLCV. They consisted of 7 plants from C47-7 line, 11 plants from L84-2 line, 9 plants from L84-23 line, and 8 plants from L120-19 line. PCR analysis confirmed that the resistant plants obtained from this study were negatively infected by the virus. Since not all tested plants were resistant to virus infection, the PCNA gene allele in these resistant lines were most likely heterozigotes. Sequencing of PCNA gene of the resistant lines is needed to confirm that the resistance phenotypes obtained was due to mutation of the gene. Therefore, further selection needs to be performed to obtain stable and PepYLCV-resistant lines.